2011
DOI: 10.1097/coc.0b013e3181e8420b
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Chemotherapy and Intensity-Modulated Radiotherapy for Organ Preservation of Locoregionally Advanced Oral Cavity Cancer

Abstract: Concurrent chemoIMRT results in promising locoregional control for oral cavity squamous cell carcinomas with acceptable toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
37
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 37 publications
6
37
1
2
Order By: Relevance
“…The rate of osteoradionecrosis in the present study was 6.8%, which falls in line with other studies – ranging from 5.9% to 18.4% – in which both conventional and IMRT were utilized [9,25]. However, as IMRT has been shown to afford lower rates osteoradionecrosis, rates in modern IMRT series have dropped to between 1% and 14% [14,15,26,27]. In patients who are surgical candidates, however, post-operative IMRT rather than IMRT alone may provide the greatest benefit [15].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The rate of osteoradionecrosis in the present study was 6.8%, which falls in line with other studies – ranging from 5.9% to 18.4% – in which both conventional and IMRT were utilized [9,25]. However, as IMRT has been shown to afford lower rates osteoradionecrosis, rates in modern IMRT series have dropped to between 1% and 14% [14,15,26,27]. In patients who are surgical candidates, however, post-operative IMRT rather than IMRT alone may provide the greatest benefit [15].…”
Section: Discussionsupporting
confidence: 89%
“…The use of IMRT has shown promise in improving patient outcomes; rates of LRC have even exceeded 90% in smaller studies utilizing CCRT with IMRT rather than 3DCRT [14]. The rate of osteoradionecrosis in the present study was 6.8%, which falls in line with other studies – ranging from 5.9% to 18.4% – in which both conventional and IMRT were utilized [9,25].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Retrospective analysis of three small phase II studies evaluating outcomes after definitive CRT for OCSCC showed 5-year overall survival rates of 56 -76%, death as a result of CRT occurring in 7.2 - 7.6%, and ORN in 14 -18% of their patient population. 16-18 These results demonstrate better OS compared to our IS cohort, but survival appears to be equivocal or worse compared to our surgical cohort in regards to OS. Additionally, there were higher rates of treatment related deaths and post-treatment complications in both our IS cohort and these IS and CRT trials compared to our surgical cohort.…”
Section: Discussionsupporting
confidence: 44%